Research of the unrecognised functions of miR-375 in prostate cancer cells: Research on the effects of miR-375 in PCa - Goztepe, Merve; Eroglu, Onur (Cellular and Molecular Biology, 2024)
Many cancers, including prostate cancer, have miRNAs with altered expression levels. These miRNAs play a pivotal role in regulating cancer initiation, invasion, and metastasis. miRNAs are an important component in cancer diagnosis and therapy and can play a key role as biomarkers or chemotherapeutic agents. This investigation aimed to show the effects of miR-375 on PCa. In this project, target prediction tools and the KEGG pathway were performed to determine the potential targets of miR-375. Transfection was performed using miR-375 mimic and inhibitor. The actions of miRNAs on cell viability and migration were examined in PCa cells. In addition, qRT-PCR was executed to evaluate changes in gene expression in the PI3K-mTOR pathway. The analyses exposed that the upregulation of miR-375 repressed the viability at 48 h. While stimulation of miR-375 did not repress the migration, suppression of miR-375 reduced the migration at 24 and 48 hours. The predicted target TSC1 gene is not directly targeted by miR-375. Interestingly, in response to PIK3CA increase, mTOR expression was suppressed in all cells except LNCAP cells. In conclusion, miR-375 has anti-proliferative and cell migration inhibitory effects in prostate cancer. However, studies demonstrate that miR-375 may have tumor suppressor and oncogenic effects when considering cell molecular differences.